“There’s Something Missing Here…”: Milo Rau, Opera, and the Search for the Real (Mozart) (Sound Stage Screen, 2022)
Review of La clemenza di Tito, music by Wolfgang Amadeus Mozart, libretto by Caterino Mazzolà. Orchestre de la Suisse Romande conducted by Maxim Emelyanychev. Stage direction by Milo Rau. Live streaming on February 19, 2021, GTG Digital.Creative team: Anton Lukas, set designer; Ottavia Castellotti, costume designer; Jürgen Kolb, light designer; Moritz von Dungern, videos; Clara Pons, dramaturg; Alan Woodbridge, choir director.Cast: Bernard Richter, Tito; Serena Farnocchia, Vitellia; Anna Goryachova, Sesto; Cecilia Molinari, Annio; Marie Lys, Servilia; Justin Hopkins, Publio.
Keywords: Theater; Opera; Milo Rau; Mozart; Lacan